Analisis Kinerja Manajemen Persediaan pada Perusahaan Danone - Steven Julianto Situmeang; Dedi Rohendi; Hanissa Okitasari (Jurnal Industri dan Teknologi Samawa, 2025)
Inventory is one of the important aspects of a company's operations, especially in meeting consumer needs efficiently. However, suboptimal inventory management can lead to excess or shortage of stock that has an impact on the company's performance. This research was conducted on DANONE, a multinational company that produces food and beverages and operates in 130 countries. This study aims to measure the company's inventory management performance in the last two years using the inventory turnover, days inventory, and inventory to revenue methods. The results show that DANONE's inventory management performance is relatively low, with a decrease in inventory turnover from 6.44 in December 2021 to 3.07 in June 2022. This decline indicates a slowdown in sales and overstock as the main problem. The conclusions of this study show the need to improve inventory management in order to increase efficiency and support the achievement of company goals.